2014
DOI: 10.1111/cpf.12219
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial uptake of bone scintigraphic agents associated with increased pulmonary uptake

Abstract: Cardiac uptake of bone scintigraphic agents is associated with high pulmonary uptake. This may be a sign of pulmonary involvement which may give extraosseous bone tracer uptake its own importance and DPD a new role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…As previously suggested by Bach-Gansmo et al [17] bone tracer lung retention could reflect blood-pool activity or relatively high local concentration in pulmonary tissue as part of soft tissue uptake in systemic amyloidosis.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…As previously suggested by Bach-Gansmo et al [17] bone tracer lung retention could reflect blood-pool activity or relatively high local concentration in pulmonary tissue as part of soft tissue uptake in systemic amyloidosis.…”
Section: Discussionmentioning
confidence: 61%
“…Few reports have mentioned in the past bone tracers lung retention both in patients with AL and TTR amyloidosis [15][16][17][18]. Nevertheless no comprehensive study has been conducted to assess lung uptake in systemic amyloidosis and its correlation with cardiac uptake.…”
Section: Introductionmentioning
confidence: 99%
“…As opposed to 99m Tc-PYP, studies have shown that the H/CL ratio in 99m Tc-HMDP imaging may be confounded by background noise with increased 99m Tc-HMDP described in soft tissue, predominantly muscles, in gluteal, shoulder, chest, abdominal wall, liver, skeletal muscle, and lung tissues,. [14][15][16] As such, use of the H/CL ratio is not recommended for HMDP. In addition, there may be differences between 99m Tc-HMDP and 99m Tc-PYP in the ability to image extracardiac amyloidosis.…”
Section: Differences In Interpretation Between 99m Tc-hmdp and 99m Tc...mentioning
confidence: 99%
“…In ATTR amyloidosis, lung involvement is considered to be rare, but histopathological findings such as amyloid deposit in the alveolar walls, pleural effusions, and lung nodules, have been reported in post mortem studies and case reports [ 11 – 16 ]. Likewise, scintigraphy studies using 99m Tc-phosphate derivatives to diagnose cardiac amyloidosis have consistently revealed some grade of lung retention in ATTR and AL amyloidosis [ 17 21 ]. New amyloid radiotracers which are well-established for imaging beta amyloid are emerging as promising tools to evaluate other forms of systemic amyloid deposition.…”
Section: Introductionmentioning
confidence: 99%